2020
DOI: 10.1159/000509628
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Vitamin E Intake Was Inversely Associated with Hyperuricemia in US Adults: NHANES 2009–2014

Abstract: <b><i>Introduction:</i></b> Current evidence on the association between dietary vitamin E intake and hyperuricemia risk is limited and conflicting. <b><i>Objective:</i></b> The aim of the study was to assess the association of dietary vitamin E intake with hyperuricemia in US adults. <b><i>Methods:</i></b> We conducted a cross-sectional study using data from the National Health and Nutrition Examination Survey, 2009–2014. Dietary vitamin E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Further analyses of OBS subclasses demonstrated the significant negative associations of dietary and lifestyle OBS with HUA. Multiple dietary nutrient intake including B group vitamins, such as vitamin B6, vitamin B12, and folate, and other nutrients such as fiber, retinol, zinc, magnesium, vitamin C, and vitamin E has been proven to be negatively correlated with HUA risk, while dietary fat intake is suggested to be positively related to HUA risk in men with CKD (47)(48)(49)(50)(51)(52)(53)(54). Nevertheless, dietary OBS was significantly associated with HUA but not gout, and more high-quality studies such as randomized controlled trials and prospective cohort studies are urged to verify the validity of our results and explore possible mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Further analyses of OBS subclasses demonstrated the significant negative associations of dietary and lifestyle OBS with HUA. Multiple dietary nutrient intake including B group vitamins, such as vitamin B6, vitamin B12, and folate, and other nutrients such as fiber, retinol, zinc, magnesium, vitamin C, and vitamin E has been proven to be negatively correlated with HUA risk, while dietary fat intake is suggested to be positively related to HUA risk in men with CKD (47)(48)(49)(50)(51)(52)(53)(54). Nevertheless, dietary OBS was significantly associated with HUA but not gout, and more high-quality studies such as randomized controlled trials and prospective cohort studies are urged to verify the validity of our results and explore possible mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…An in vitro study reported that vit C and vit E could inhibit XO activity. Studies have also suggested a negative association between vit E and HUA [ 12 , 13 , 32 ]. Similar associations and mechanisms have also been reported for dietary Zn [ 14 , 33 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…The cross-sectional study evaluated the association of dietary vitamin E intake with hyperuricemia in US adults. The results indicated that it was negatively correlated with hyperuricemia, especially among males and participants aged ≥60 years [43]. Uric acid-lowering effect might be also observed in a vitamin D-rich diet.…”
Section: Vitamin Supplementation In the Treatment Of Goutmentioning
confidence: 90%